Attitudes towards severe mental illness and social distance: A survey of volunteer befrienders in Austria. (August 2018) - Toner, Sarah; Fabisch, Karin; Priebe, Stefan; Klug, Gϋnter
Background: Research suggests there is a propensity for people in the general population to distance themselves from people with severe mental illness (SMI), which reportedly decreases with increased contact with individuals with SMI. Volunteer befrienders in the mental health sector have ongoing contact with this population, yet little data exist to reflect their attitudes towards people with SMI. Method: A questionnaire was distributed to all volunteer befrienders for people with SMI within volunteering programmes organised in five Austrian regions. A vignette described an individual with SMI and was followed by questions assessing willingness to interact with this person in personal or professional contexts. Social distance scores, calculated based on responses to attitude items, were used as the dependent variable in regression analyses. Independent variables included participant characteristics, experience of family/friends with mental illness, time spent befriending and satisfaction with the relationship. Results: Questionnaires were completed and returned by 360 volunteers (54.0%). A minority would allow someone with SMI to look after their children (6.2%), while most volunteers positively endorsed other personal interactions such as having the individual marry into their family (67.8%) or become a neighbour (99.7%). Social distance ( M = 2.5, standard deviation [ SD ] = 1.16) was not associated with any independent variables. Conclusions: Volunteers had a lower desire for social distance from individuals with SMI as compared to findings from the general population. Future research may establish whether lower social distance is part of the motivation to volunteer as a befriender to people with severe mental illness or develops over time in that role or both.